Development of sex- and genotype-specific behavioral phenotypes in a Shank3 mouse model for neurodevelopmental disorders - Bauer, Helen Friedericke; Delling, Jan Philipp; Bockmann, Jürgen; Boeckers, Tobias M.; Schön, Michael (Frontiers in Behavioral Neuroscience, 2023)
Individuals with a SHANK3-related neurodevelopmental disorder, also termed Phelan-McDermid syndrome or abbreviated as PMS, exhibit significant global developmental delay, language impairment, and muscular hypotonia. Also common are repetitive behaviors and altered social interactions, in line with a diagnosis of autism spectrum disorders. This study investigated the developmental aspect of autism-related behaviors and other phenotypes in a Shank3-transgenic mouse model. The animals underwent two sets of identical behavioral experiments, spanning motor skills, social and repetitive behavior, and cognition: baseline began at 5 weeks of age, corresponding to human adolescence, and the follow-up was initiated when aged 13 weeks, resembling early adulthood in humans. Interestingly, the animals displayed relatively stable phenotypes. Moreover, motor coordination and endurance were impaired, while muscle strength was unchanged. Surprisingly, the animals displayed only minor impairments in social behavior, but pronounced stereotypic and repetitive behaviors. Some behavioral tests indicated increased avoidance and anxiety. While spatial learning and memory were unchanged, knockout animals displayed slightly impaired cognitive flexibility. Female animals had similar abnormalities as males in the paradigms testing avoidance, anxiety, and cognition, but were less pathological in motor function and repetitive behavior. In all test paradigms, heterozygous Shank3 knockout animals had either no abnormal or a milder phenotype. Accurate characterization of animal models for genetic diseases is a prerequisite for understanding the pathophysiology. This is subsequently the basis for finding suitable and, ideally, translational biomarkers for therapeutic approaches and, thereby reducing the number of animals needed for preclinical trials.